Effect of Echium amoenum Fisch. et Mey a Traditional Iranian Herbal Remedy in an Experimental Model of Acute Pancreatitis. (13th September 2012) - Abed, Alireza; Minaiyan, Mohsen; Ghannadi, Alireza; Mahzouni, Parvin; Babavalian, Mohammad Reza
Abstract : Acute pancreatitis is a morbid inflammatory condition of pancreas with limited specific therapy. Enhanced oxidative stress plays an important role in induction and progression of acute pancreatitis. So reducing oxidative stress may relieve this pathogenic process. Echium amoenum Fisch. and Mey has been implemented in Iranian folk medicine for several centuries. Antioxidant, analgesic, immunomodulatory, and anxiolytic properties of E. amoenum suggest that this plant may have beneficial effects in the management of acute pancreatitis. The aim of this study was to evaluate the protective effect of petals of E. amoenum extract (EAE) on a murine model of pancreatitis. Acute pancreatitis was induced by five intraperitoneal (i.p.) injection of cerulein (50  μ g/kg) with 1h intervals which was characterized by pancreatic inflammation and increase in the serum level of digestive enzymes, in comparison to normal mice. EAE (100, 200, and 400 mg/kg) was administered i.p., 30 minutes before induction of pancreatitis. Pretreatment with EAE (400 mg/kg) reduced significantly the inflammatory response of cerulein-induced acute pancreatitis by ameliorating pancreatic edema, amylase and lipase serum levels, proinflammatory cytokines, myeloperoxidase activity, lipid peroxidation and pathological alteration. These results show that EAE attenuates the severity of cerulein-induced acute pancreatitis with an anti-inflammatory, immunomodulatory and antioxidant effects.